Wireless Sensor Networks Architecture - Applications - Advancements - Vijayalakshmi, S. R. (Mercury Learning and Information, 2018)
Wireless Sensor Networks is an essential guide for anyone interested in wireless communications for sensor networks, home networking, or device hacking. It covers a large number of topics encountered in the architecture, application, and recent advancements of a wireless sensor network, including hardware and software architectures, the Internet of Things, routing and security, MANETs, MEMS, Zigbee, TDMA, securing networks for WiFi, ubiquitous sensor networks, underwater, mobile, and multimedia wireless networks. Features:• Includes a wide range of applications to industry, science, transportation, civil infrastructure, and security • Covers the Internet of Things (IoT), MEMS, Zigbee, TDMA, mobile wireless networks, and more • Features article on securing networks for WiFi by the United States Department of Homeland Security (DHS) Cybersecurity Engineering